Catalytic Access to Alkyl Bromides, Chlorides and Iodides via Visible Light‐Promoted Decarboxylative Halogenation. Issue 29 (8th June 2016) - Candish, Lisa; Standley, Eric A.; Gómez‐Suárez, Adrián; Mukherjee, Satobhisha; Glorius, Frank
Abstract: Herein is reported the catalytic, visible light‐promoted, decarboxylative halogenation (bromination, chlorination, and iodination) of aliphatic carboxylic acids. This operationally‐simple reaction tolerates a range of functional groups, proceeds at room temperature, and is redox neutral. By employing an iridium photocatalyst in concert with a halogen atom source, the use of stoichiometric metals such as silver, mercury, thallium, and lead can be circumvented. This reaction grants access to valuable synthetic building blocks from the large pool of cheap, readily available carboxylic acids. Abstract : Br‐ight approach : The catalytic, visible light‐mediated, decarboxylative bromination, chlorination, and iodination of aliphatic carboxylic acids is reported. This transformation requires no stoichiometric heavy metals and provides access to valuable synthetic building blocks starting from the large pool of readily available aliphatic carboxylic acids.